A facile hydrothermal method for preparation of fluorescent carbon dots on application of Fe3+ and fingerprint detection. (11th April 2019) - Feng, Rui-Qi; Yuan, Zhong-Yong; Ren, Tie-Zhen
Abstract: The carbon dots (CDs) was prepared by a facile hydrothermal treatment of citric acid and glycine at 180 °C. The CDs at around 3.2 nm was collected after filtration and dialysis. The sample displayed green fluorescence (G-CDs) with a quantum yield of 3.7% in high concentration and the strongest emission peak was at 545 nm under the excitation wavelength of 480 nm; the blue fluorescence CDs (B-CDs) with a quantum yield of 29.8% was obtained after diluted either in solution or in powder, the strongest emission peak was located at 475 nm under the excitation wavelength of 380 nm. The G-CDs possessed a high selectivity to Fe 3+, which was in a linear range of 0–3.5 μ M with the detection limit of 0.21 μ M. The CDs powder with blue fluorescence at a relative low content was obtained and adaptable for the fingerprint detection on substrates of litmus paper, resin tabletop, glass, and orange plastic ruler.